Yellia Tomasoa The Effect of Learning Model and Motivation on Long Jump Learning Outcomes: The Effect of Learning Model and Motivation on Long Jump Learning Outcomes - Yellia Tomasoa; Falerius Somarwain; Mariana Ditboya Hukubun (UNIB Press, 2025)
This study aims to analyze the effect of Visual, Audiotorial, and Kinesthetic learning styles on the learning outcomes of movement skills of grade II students of Dobo Christian Elementary School 1, Data collection was carried out using a questionnaire. The population in this study amounted to 60 students and a sample of 36 students determined by random sampling technique or randomly. This research is an experimental expo-facto research, the analysis technique used uses inferential analysis techniques. The results obtained are that there is an influence between Visual, Audiotorial, and Kinesthetic learning styles on the learning outcomes of students' movement skills as evidenced by statistical analysis which is 6.926. Thus, Visual, Audiotorial, and Kinesthetic learning styles have a positive effect on student movement skills learning outcomes as evidenced by statistical analysis tests.